2017
DOI: 10.1016/s1470-2045(17)30246-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-dose radiotherapy for human papillomavirus-associated squamous-cell carcinoma of the oropharynx: a single-arm, phase 2 study

Abstract: University of California.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
218
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(234 citation statements)
references
References 42 publications
(44 reference statements)
8
218
0
2
Order By: Relevance
“…4 The HPVrelated OPC has different characteristics from classic HNSCC, which is caused by habitual smoking and alcohol consumption. 6,7 In contrast, the prognostic role of HPV status in non-OPC remains to be determined. 6,7 In contrast, the prognostic role of HPV status in non-OPC remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…4 The HPVrelated OPC has different characteristics from classic HNSCC, which is caused by habitual smoking and alcohol consumption. 6,7 In contrast, the prognostic role of HPV status in non-OPC remains to be determined. 6,7 In contrast, the prognostic role of HPV status in non-OPC remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have reported that reduced radiation therapy is feasible for children and adolescents with NPC-and HPV-positive oropharyngeal cancer, 8,9,11,17,18 it is unclear whether reduced-dose radiation for adults with NPC with IMRT can achieve satisfactory results. Although some studies have reported that reduced radiation therapy is feasible for children and adolescents with NPC-and HPV-positive oropharyngeal cancer, 8,9,11,17,18 it is unclear whether reduced-dose radiation for adults with NPC with IMRT can achieve satisfactory results.…”
Section: Discussionmentioning
confidence: 99%
“…11 Fortyfour patients with complete or partial remission to IC received chemoradiotherapy with 54 Gy radiation doses. NPC-and HPVpositive oropharyngeal cancer are both virus-related tumors and are sensitive to radiotherapy and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, patients without external beam radiation therapy at doses of 54 to 75 Gy or failing to complete the course of radiation between 25 and 75 days were excluded to omit patients with untrusted dosing and time intervals. A lower threshold of 54 Gy was used, as this is the lowest dose to date tested to our knowledge . Patients with follow‐up of ≤2 months were excluded to account for immortal time bias.…”
Section: Methodsmentioning
confidence: 99%